A look at the magical thought of Giordano Bruno - Sánchez Aguirre, Flor de María; Depaz Toledo, Silvestre Zenón (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
The objective of the study was to systematize and analyze Bruno’s philosophical thought on the conception of magic in the Renaissance. The importance of the research was to understand the Bruneian worldview that is still valid in the development of the advancement of science. Being the conclusion that the concept of magician is equivalent to sage and is manifested through the types of magic: Divine, Physical, Mathematical and depending on the link between the magician and nature: natural magic, phantasmagoric, natural magic by virtue, mathematical magic, of the forsaken, necromancy, evil, divination and prophecy.